Nutrition for Adolescent Female Team Sport Athletes: A Review. Issue 4 (August 2020) - Sharples, Alice; Baker, Dane; Black, Katherine
Abstract : ABSTRACT: Adequate nutrition generally promotes training adaptations and thus optimal performance. Adolescence is characterized by a pubescence growth spurt, increasing energy and nutrient needs. Most team sports literature focuses on male athletes, with little on adolescent female team sports. Adolescent female athletes are at an increased risk of inadequate energy, and micronutrient intakes because of the pursuit of high fitness levels, and society pressures. This may cause hormonal irregularities, delayed development, poor bone health, and increased risk of injury. This review synthesizes information on the nutritional needs of adolescent female team sport players for performance and health.